Day to Day Economics - Satish Y Deodhar; DEODHAR (Satish Y) (Haryana Penguin Random House India Pvt Ltd, 2018)
The economy isnt just for the economics to debate on. All of us are affected by its ups and downs - global recession, rise in interest rates, or hike in food prices. But do we understand the principles at work and how and why they really affect us? Day to day economics is an enjoyable, accessible, and extremely user-friendly book that explains modern day Indian economy to The economy isnt just for the economics to debate on. All of us are affected by its ups and downs - global recession, rise in interest rates, or hike in food prices. But do we understand the principles at work and how and why they really affect us? Day to day economics is an enjoyable, accessible, and extremely user-friendly book that explains modern day Indian economy to the layperson. In this relevant book, Professor Deodhar explains the role of the government and its involvement in different aspects of the economy; the need for the RBI and its functions; and how taxes, stock markets and recession work. Day to Day Economics will help you go beyond the facts and figures in the budget and connect the trends to your daily life. As with all IIMA business books, it comes illustrated with numerous Indian examples and case studies making this the ultimate rookies guide to the Indian economy.
Keywords: Economic history; Economics; Economic policy; India; IIM Ahmedabad